Impacts of the perioperative fast track surgery concept on the physical and psychological rehabilitation of total hip arthroplasty: A prospective cohort study of 348 patients. Issue 32 (13th August 2021) - Zhong, Meiyan; Liu, Dehuai; Tang, Haijun; Zheng, Yadong; Bai, Yu; Liang, Qinghua; Yang, Xining
Abstract : Abstract: Studies have shown that rapid rehabilitation surgery has a positive effect on recovery after major orthopedic surgery. However, very few studies have examined the impact of fast track surgery on physical and psychological rehabilitation in patients who have undergone total hip replacement. This study aimed to investigate the value of the rapid rehabilitation surgical model for patients undergoing total hip arthroplasty during the perioperative period. We conducted a prospective cohort study that included patients who underwent total hip arthroplasty at our hospital from January 2015 to December 2018. We divided the patients into 2 groups – the rapid rehabilitation group and the conventional rehabilitation group – and compared their length of hospital stay, time to off-bed activity, pain score, Self-Rating Anxiety Scale scores, Self-Rating Depression Scale scores, complication rate, and rate of satisfaction during hospitalization. A total of 348 patients were included in the study. Of these, 180 received rapid rehabilitation nursing and 168 patients received conventional nursing. Compared with the patients in the conventional rehabilitation group, those in the rapid rehabilitation group had shorter hospital stays (11.5 ± 1.2 day vs 15.5 ± 2.3 day, P  = .021), resumed off-bed activities sooner (20.5 ± 3.4 hours vs 61.8 ± 4.7 hours, P  = .001, had less postoperative pain (4.0 ± 1.2 vs 6.5 ± 1.1, P  < .001), and lower anxiety and depression scores (anxiety score: 24.4 ± 2.1 vs 47.9 ± 2.9; depression score: 25.8 ± 1.8 vs 43.7 ± 1.7, P  < .001). The application of rapid rehabilitation surgery in total hip arthroplasty can accelerate patients' postoperative recovery, relieve anxiety and depression, and increase the patient's satisfaction with the treatment.